Multifrequency study of a new Fe-rich supernova remnant in the Large Magellanic Cloud, MCSNR J0508-6902 - Bozzetto, L. M.; Kavanagh, P. J.; Maggi, P.; Filipovic, M. D.; Stupar, M.; Parker, Q. A.; Reid, W. A.; Sasaki, Manami; Haberl, F.; Urosevic, D.; Dickel, J.; Sturm, R.; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
We present a detailed radio, X-ray and optical study of a newly discovered Large Magellanic Cloud (LMC) supernova remnant (SNR) which we denote as MCSNR J0508-6902. Observations from the Australia Telescope Compact Array (ATCA) and the XMM-Newton X-ray observatory are complemented by deep Ha images and Anglo-Australian Telescope AAOmega spectroscopic data to study the SNR shell and its shock ionization. Archival data at other wavelengths are also examined. The remnant follows a filled-in shell-type morphology in the radio continuum and has a size of similar to 74 pc x 57 pc at the LMC distance. The X-ray emission exhibits a faint soft shell morphology with Fe-rich gas in its interior - indicative of a Type Ia origin. The remnant appears to be mostly dissipated at higher radio-continuum frequencies leaving only the south-eastern limb fully detectable while in the optical it is the western side of the SNR shell that is clearly detected. The best-fitting temperature to the shell X-ray emission (kT = 0.41(-0.06)(+0.05) keV) is consistent with other large LMC SNRs. We determined an O/Fe ratio of <21 and an Fe mass of 0.5-1.8 M-circle dot in the interior of the remnant, both of which are consistent with the Type Ia scenario. We find an equipartition magnetic field for the remnant of similar to 28 mu G, a value typical of older SNRs and consistent with other analyses which also infer an older remnant.
Keywords: ISM: supernova remnants; Magellanic Clouds; radio continuum: ISM; X-rays: ISM